Educational Management Strategies in Drama Learning: The Role of Role-Playing Models and Literary Reading Interest in Improving Students’ Drama Performance Ability - Yunia Kurminarsih (Al-Qalam Institue, 2026)
Drama performance serves as an important medium for developing students’ life skills, including adaptability, social interaction, and problem-solving abilities through experiential learning. This study aims to analyze the influence of the Role-Playing learning model and students’ interest in reading literary works on drama performance skills within the framework of instructional management in schools. The research employed an experimental method using a 2×2 treatment by level design and was conducted at MAS Al-Nahdlah Depok. The sample consisted of two classes: an experimental class taught using the Role-Playing model and a control class taught using the ARIAS learning model. Data were collected through questionnaires to measure students’ literary reading interest and performance rubrics to assess drama acting skills, including vocal ability, expression, emotional engagement, gesture, and improvisation. Data analysis was carried out using two-way ANOVA followed by Tukey’s post hoc test at a significance level of α = 0.05. The results indicate that students taught using the Role-Playing model demonstrated significantly higher drama performance skills compared to those taught using the ARIAS model, particularly among students with lower literary reading interest. These findings imply that effective instructional management, through the selection of appropriate learning models aligned with students’ characteristics, plays a strategic role in enhancing drama learning outcomes. Therefore, educational management should integrate pedagogical strategies such as role-playing and literacy considerations into learning planning and implementation to optimize students’ performance and life-skill development